2018
DOI: 10.1155/2018/3614341
|View full text |Cite
|
Sign up to set email alerts
|

Soluble HLA-I and HLA-II Molecules Are Potential Prognostic Markers of Progression of Systemic and Local Inflammation in Patients with COPD

Abstract: Soluble molecules of the major histocompatibility complex play an important role in the development of various immune-mediated diseases. However, there is not much information on the participation of these proteins in the pathogenesis of chronic obstructive pulmonary disease (COPD). The aim of our work was to determine the content of soluble molecules of the major histocompatibility complex of classes I and II (sHLA-I and sHLA-II) in the exhaled breath condensate (EBC) and in the blood serum in patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…We also identified several COPD-associated genes enriched for immune processes and immune-related diseases (e.g., HLA-C and HLA-DQB1-antigen processing and presentation, HLA-DQB1-type I diabetes mellitus, influenza A, autoimmune thyroid disease) (Table S5). This finding is consistent with observations that proteins of the major histocompatibility complex of classes I and II (HLA-I and HLA-II) have been identified as potential markers of progression of systemic and local inflammation in patients with COPD (Kubysheva et al, 2018). Specifically, an increase in the level of HLA-I and HLA-II molecules in the exhaled breath condensate as well as an elevated serum level of HLA-II is observed in COPD patients when compared with healthy volunteers (Kubysheva et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…We also identified several COPD-associated genes enriched for immune processes and immune-related diseases (e.g., HLA-C and HLA-DQB1-antigen processing and presentation, HLA-DQB1-type I diabetes mellitus, influenza A, autoimmune thyroid disease) (Table S5). This finding is consistent with observations that proteins of the major histocompatibility complex of classes I and II (HLA-I and HLA-II) have been identified as potential markers of progression of systemic and local inflammation in patients with COPD (Kubysheva et al, 2018). Specifically, an increase in the level of HLA-I and HLA-II molecules in the exhaled breath condensate as well as an elevated serum level of HLA-II is observed in COPD patients when compared with healthy volunteers (Kubysheva et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Since their discovery, many have tried to find explanations for the altered sHLA levels in malignancies and their association with disease progression and prognosis. In addition to malignancies, altered sHLA levels have been observed in chronic disease [ 82 ], autoimmunity [ 83 , 84 ], and viral infections [ 85 , 86 ]; strongly suggesting that there are shared inflammatory pathways that regulate sHLA. Knowing how sHLA-I and sHLA-II release is regulated and to what extent these complexes affect immune responses is crucial to determine whether their increased presence is merely a consequence of ongoing immunity or whether they also partake in pathophysiological processes.…”
Section: Shla Complexes: Mechanism Of Secretion and Immunological mentioning
confidence: 99%
“…The only COPD related statistically signi cant difference in the MS analysis was an upregulation of HLA-A. Increased HLA-A protein have previously been found in exhaled breathe condensate of COPD patients, another study found increased gene expression in both AEC2 and in blood samples of COPD patients 44,45 . Our results both support HLA-A as a potential COPD biomarker and indicate that the AEC2 retain characteristics of their origin in this culture system.…”
Section: Discussionmentioning
confidence: 76%